How Could Construction Industry Revive Thai Economy? : Resurrection with Economic and Human Values from Design Professions - Rojanavanich, Pisit (Journal of Architectural/Planning Research and Studies (JARS), 2002)
After the economic crisis in 1997, Design, Construction, and related field like Real Estate Development Industry have consistently been in a state of depression, with no sign of solid recovery on the horizon. At the moment, concerted efforts from various associations of Design, Construction, and Real Estate Development Professions are being made to seek the assistance from the government in rejuvenating the Design & Construction Industry through various measures. This paper is aiming to pinpoint what went wrong with the last Design & Construction boom period between 1987-1997. It is clear now that the last boom represents the investment driven cycle whereby value added aimed at was purely economic. The human values manifested in livable built environment development and the increase of human capability of the professions involved were weak if not absent. The missing values were very critical in increasing the competitive capability of the country in terms of tourism, investment, and the export of design & service industry. Moreover, Thai people will also enjoy the better quality of built environments. As such, if measures are to be made to reactivate the Design and Construction Industry, deep thoughts and strategies are necessary for meaningful and successful outcomes with both economic and human values. Short term thinking emphasizing on immediate survival would not suffice.